Oligoetherols and polyurethane foams with 1,3,5-triazine ring and boron atoms - Lubczak, J.; Łukasiewicz, B. (Polimery, 2012)
Oligoetherols containing 1,3,5-triazine ring and boron atoms were synthesized in the reactions of N,N,N’,N’,N”,N”-hexakis(2-hydroxyethyl)melamine with boric acid, followed by reaction with alkylene carbonates. The structure and physical properties of the obtained oligoetherols were investigated. The oligoetherols were used for the preparation of polyurethane foams with improved thermal stability and reduced flammability. The properties of obtained foams were compared with those synthesized directly from melamine and alkylene carbonates.